字体摩登 : 字体书与中国现代文字设计的再发现 1919-1955 - 周博 - Zhou Bo, ....-; 吴帆 - Wu Fan, ....-; 刘畅 - Liu Chang, ....- (北京 : 中信出版社, 2017)
[p. IV] This book, ‘Chinese Type Modern', examines and reflects on the history of modern Chinese type design over a period from 1919 to 1955, referencing more than seventy Chinese publications on the issue of typeface design, starting from ‘Modern Chinese Artistic Typefaces' [现代美术字] in 1919 to 'Information of Applied Artistic Typefaces' [应用美术字资] in 1955. Within the roughly three decades modern Chinese typography had gone from birth to its maturity, spanning various periods including the Nanjing National Government's “golden decade” of economic development (1927-1937), War of Resistance against Japan (1937-1945), Liberation War and the first five years since the founding of New China, during each period Chinese typography developed exclusive styles bearing deep imprints of socio-economic and political changes. Based on found materials ‘Chinese Type Modern' gives a brief account of the birth and development of Chinese artistic typefaces, analyzing its evolution within socio-political contexts. The author especially points out that typefaces from that period differ so much from what we are accustomed to use today because during that time traditional Chinese characters prevailed and most typeface designers were informed by the habit of traditional calligraphy. Those days was, in fact, a grand transitional period, culturally and typographically speaking, when new and old types clashed and merged. In addition, the author believes that these publications and their hightened sense of typeface aesthetics reflects the achievements of the age and defines what we term “modern Chinese type design”, hence the name “Type Modern”. Further, the author advocates the revival of Chinese artistic typeface and typography and believes that contemporary designers can benefit from an enriched knowledge and deepened understanding of Chinese typeface design, adding to the uniqueness and diversity of contemporary Chinese typography.
Bevat los uitvouwblad Foundertype 2016 fonts
附件：2016方正字库字体样本